PENINGKATAN LITERASI KESEHATAN DIGITAL DALAM UPAYA PENCEGAHAN MISINFORMASI KESEHATAN MASYARAKAT - Agustina Retno Hapsari; Fahmi Baiquni; Laily Mualifah; Nur Cahya Rachmawati; Mizan Prihastuti (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2026)
The rapid development of digital technology has made digital media a primary source of health information for the public. However, easy access to information also increases the risk of health misinformation, which may negatively affect health-related decision making. This activity aimed to improve community digital health literacy to prevent health misinformation through an educative–participatory approach. A pre-experimental design with a one group pre-test and post-test was applied. The intervention consisted of interactive education sessions, group discussions, and case studies using common health information found on social media platforms. The results indicated improvements in participants’ knowledge, critical attitudes, and ability to evaluate the credibility of digital health information. Participants became more cautious and selective in accepting and sharing health-related content. These findings suggest that strengthening digital health literacy is an effective promotive and preventive strategy to address health misinformation challenges in the digital era.